A Case of Critically Ill Infant of Coronavirus Disease 2019 With Persistent Reduction of T Lymphocytes. Issue 7 (July 2020) - Qiu, Liru; Jiao, Rong; Zhang, Aiming; Chen, Xi; Ning, Qin; Fang, Feng; Zeng, Fang; Tian, Niannian; Zhang, Yi; Huang, Yafei; Sun, Ziyan; Dhuromsingh, Menaka; et al.
Abstract : Background: The outbreak of coronavirus disease 2019 (COVID-19) is becoming a global threat. However, our understanding of the clinical characteristics and treatment of critically ill pediatric patients and their ability of transmitting the coronavirus that causes COVID-19 still remains inadequate because only a handful pediatric cases of COVID-19 have been reported. Methods: Epidemiology, clinical characteristics, treatment, laboratory data and follow-up information and the treatment of critically ill infant were recorded. Results: The infant had life-threatening clinical features including high fever, septic shock, recurrent apnea, petechiae and acute kidney injury and persistent declined CD3+, CD4+ and CD8+ T cells. The duration of nasopharyngeal virus shedding lasted for 49 days even with the administration of lopinavir/ritonavir for 8 days. The CD3+, CD4+ and CD8+ T cells was partially recovered 68 days post onset of the disease. Accumulating of effector memory CD4+ T cells (CD4+TEM) was observed among T-cell compartment. The nucleic acid tests and serum antibody for the severe acute respiratory syndrome coronavirus 2 of the infant's mother who kept intimate contact with the infant were negative despite no strict personal protection. Conclusions: The persistent reduction of CD4+ and CD8+ T cells was the typical feature of critically ill infant with COVID-19. CD4+ and CD8+ T cells might play a key role in aggravating COVID-19 and predicts a more critical course in children. The prolonged nasopharyngeal virus shedding was related with the severity of respiratory injury. The transmission of SARS-CoV-2 from infant (even very critical cases) to adult might be unlikely. Abstract : Supplemental Digital Content is available in the text.